2018
DOI: 10.3389/fimmu.2018.02894
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Role of Qa-2 and HLA-G Non-classical MHC-I Complexes in Malignancy

Abstract: It is well established that the immune system can identify and destroy neoplastic transformed cells in a process known as immunosurveillance. Most studies have focused on the classical major histocompatibility complex (MHC) class Ia molecules, which are known to play an important role on the presentation of tumor antigens to the immune system in order to activate a response against tumor cells. However, a larger family of non-classical MHC class Ib-related molecules has received less attention. In this mini-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“… 38–43 Some of the immunosuppressive roles described for these TFs include the promotion of exhausted and senescent CD8+ T cells during chronic viral infections by PRDM1, cancer-chemoresistance by the upregulation of regulatory T-cell recruitment through CEBPB, and the induction of T helper cell differentiation toward immunosuppressive Th2 cells by IRF2. 38–41 , 44 , 45 Specific pathways modulated by these TFs in relation to MR1 not yet understood.…”
Section: Discussionmentioning
confidence: 99%
“… 38–43 Some of the immunosuppressive roles described for these TFs include the promotion of exhausted and senescent CD8+ T cells during chronic viral infections by PRDM1, cancer-chemoresistance by the upregulation of regulatory T-cell recruitment through CEBPB, and the induction of T helper cell differentiation toward immunosuppressive Th2 cells by IRF2. 38–41 , 44 , 45 Specific pathways modulated by these TFs in relation to MR1 not yet understood.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that cancers can also evade immune elimination by expressing "non-classical" MHC class Ib molecules, HLA-E and HLA-G (26)(27)(28). However, since this immune evasion mechanism is not due to a loss of antigen presentation by "classical" MHC class Ia molecules, but rather through engagement of inhibitory receptors on T lymphocytes and other immune cells (26)(27)(28), this subject is not covered in this review, except as it relates to how MHC I low cancers may evade NK cell recognition. Similarly, MHC II molecules can play a role in cancer immunity, however, since MHC I and MHC II antigen presentation are separate and non-intersecting pathways, this review does not cover the MHC II pathway in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies had found no evidence of functional interaction between sHLA-G and KIR2DL4 in NK cells [ 35 ]. Therefore, whether HLA-G/KIR2DL4 interaction affects the activity of NK cells remains controversial [ 36 ].…”
Section: Hla-g Mediates Immune Regulationmentioning
confidence: 99%